Education Reform: A Strategy for a School of Success - Oussama Dardary; Zineb Azar; Malika Tridane; Said Belaaouad (Iraqi Journal of Science, 2021)
Since independence in 1956, several attempts have been made to reform educational practices in the Moroccan education system, while going through several stages:Evaluation of the state of the Moroccan education system, determination of failures and the establishment of an effective strategy to improve the quality of education and training in the Moroccan public school.We focus on monitoring the establishment of the pillars of the reform, against the various difficulties that hinder the development of the education sector, from 1999 until today and towards the horizon of 2030. We provide data on the situation of the reform, then we analyze its various stages from a critical point of view, based on the reports of the court of auditors, to arrive at final proposals.